The role of flash mathematics learning media in mathematics learning at Darur Rahmah Middle School - Kustiyowati, Kustiyowati (SAINTIS Publishing, 2023)
Learning Media is a learning tool that is used by someone with the aim of facilitating the delivery of information in learning. This is very helpful for teachers in their teaching and can be a solution to eliminating boredom when students are happy during learning activities. Flash media is a program that produces interactive and animated media that can combine images, audio, and video and give an effect that makes it interesting for students. This study aims to determine the effectiveness of flash learning media in learning mathematics at Class VII Junior High School, Darur Rahmah, Jember Regency. The method uses descriptive language by examining the teacher's ability to manage learning, responses, activities, and student learning outcomes. Based on the results of the analysis related to the effectiveness of flash learning media in mathematics learning at Darur Rahmah Junior High School, it can be concluded that (1) The ability of teachers to manage mathematics learning using flash media is categorized as very good; (2) Student activity is categorized as good with a percentage of student activity of 81.4%; (3) Student response to positive mathematics learning with a percentage of 94.29%; and (4) student learning outcomes meet the criteria of classical completeness with students completing 85.2%. Thus, the role of flash media in learning mathematics for class VII at SMP Darur Rahmah can be said to be effective.